Lithium battery composite diaphragm with high heat resistance and high breakdown field strength and preparation method of lithium battery composite diaphragm
By adopting a composite structure of a flexible continuous glass fiber skeleton and a three-dimensional crosslinked organic polymer cladding in the lithium battery separator, the problems of heat resistance and breakdown field strength of the existing separator at high temperature and high voltage are solved, and a separator with high heat resistance and high breakdown field strength is achieved, which improves the reliability and safety of the lithium battery.
Patent Information
- Application Number
- CN202510110902.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing lithium battery separators have poor heat resistance, voltage resistance and structural stability at high temperatures and high voltages, resulting in structural deterioration and even failure such as softening and shrinkage, melting and electric breakdown, which seriously restricts the reliability and safety of lithium batteries.
A composite separator consisting of a flexible continuous glass fiber frame and a three-dimensional crosslinked organic polymer cladding layer is used. The flexible continuous glass fiber frame is embedded in the three-dimensional crosslinked organic polymer cladding layer, and the polymer is crosslinked by photoirradiation to form a separator with high heat resistance and high breakdown field strength.
The heat resistance temperature of the diaphragm is improved to nearly 350℃, the breakdown field is enhanced by 140kV/mm, the electrochemical performance and preparation convenience are enhanced, and the requirements of high structural stability, high safety and high reliability of lithium batteries are met.
Smart Images

Figure CN119864600A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery separators, and in particular relates to a lithium battery composite separator with high heat resistance and high breakdown field strength and a preparation method thereof. Background Art
[0002] The diaphragm is an electrically insulating film with a microporous structure. Its function is to block the short circuit between the positive and negative electrodes and conduct ions, acting as a key safety component in secondary batteries such as lithium batteries. Commonly used lithium battery diaphragms are polyolefin diaphragms such as polyethylene PE and polypropylene PP. Such diaphragms have the advantages of excellent chemical stability, good tensile strength and low cost, but they also have problems such as poor heat resistance, low modulus and low breakdown field strength. Under harsh service conditions in scenarios such as large-scale energy storage and electric vehicles, especially under high temperature and high voltage, the corresponding battery diaphragms are very prone to structural degradation and even failure such as softening and shrinkage, melting and electrical breakdown, which seriously restricts the reliability and safety of lithium batteries.
[0003] In order to improve the thermal stability of the diaphragm, a common strategy is to use highly heat-resistant electrical insulating polymers such as polyimide, meta-aramid, polyetheretherketone, and polybenzimidazole to develop new diaphragms. However, the common problems of difficult processing and high cost of these heat-resistant polymers make them difficult to apply on a large scale. The second strategy is to develop coated diaphragms, that is, to coat a layer of inorganic particles such as alumina and boehmite or polymers such as polyvinylidene fluoride on both sides of the commercial polyolefin diaphragm to form a composite diaphragm to improve the thermal stability of the diaphragm. Although this method has improved the high temperature resistance of the diaphragm to a certain extent, its maximum operating temperature is still below 150°C, and there are still problems such as structural instability such as coating powdering or degradation of breakdown field strength due to poor bonding with the substrate. Therefore, there are still major reliability and safety risks during use.
[0004] In summary, it is necessary to develop a new type of lithium battery separator based on new material design that is resistant to high temperature and high voltage, has excellent electrochemical properties, and is easy to prepare. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a lithium battery composite diaphragm with high heat resistance and high breakdown field strength and a preparation method thereof, so as to solve the problems of poor high temperature resistance, voltage resistance and structural stability in the existing diaphragm technology. In order to achieve the above object, the present invention adopts the following technical solutions: A lithium battery composite diaphragm with high heat resistance and high breakdown field strength, the diaphragm comprising a flexible continuous glass fiber skeleton and a three-dimensional cross-linked organic polymer coating layer, wherein the flexible continuous glass fiber skeleton is embedded in the three-dimensional cross-linked organic polymer coating layer; The flexible continuous glass fiber skeleton is one or both of a flexible continuous nano glass fiber cloth and a flexible alkali-free ultrafine glass fiber cloth; The flexible continuous nano glass fiber cloth is amorphous SiO2.
[0006] A further improvement of the present invention is: Preferably, the flexible continuous nano-glass fiber cloth is composed of a plurality of fibers, the fiber diameter is 100-400 nm, and the thickness of the flexible continuous nano-glass fiber cloth is 5-50 μm.
[0007] Preferably, the flexible continuous nano-glass fiber cloth is an oriented distribution structure or a disordered non-woven structure.
[0008] Preferably, the diameter of the fibers in the flexible alkali-free ultrafine glass fiber cloth is 0.1-8 μm, and the thickness of the flexible alkali-free ultrafine glass fiber cloth is 5-50 μm.
[0009] A method for preparing the above-mentioned high heat-resistant and high breakdown field strength lithium battery composite diaphragm comprises the following steps: Step 1, selecting a flexible continuous nano-glass fiber cloth or a flexible alkali-free ultra-fine glass fiber cloth as a flexible continuous glass fiber skeleton; Step 2, mixing the prepolymer, the photoinitiator and the pore-forming agent to obtain an impregnation solution; Step 3, placing the flexible continuous glass fiber skeleton on the substrate, dripping the impregnation liquid on the flexible continuous glass fiber skeleton, and the flexible continuous glass fiber skeleton is immersed in the impregnation liquid; Step 4, irradiating the impregnating liquid and the flexible continuous glass fiber skeleton with a light source, and after the photovoltaic cross-linked cured polymer in the impregnating liquid is cured, a three-dimensional cross-linked organic polymer coating layer is obtained, in which a flexible continuous glass fiber skeleton is embedded, which is a lithium battery composite diaphragm with high heat resistance and high breakdown field strength.
[0010] Preferably, in step 1, the preparation method of the flexible continuous nano-glass fiber cloth is: tetraethyl silicate, dilute hydrochloric acid and ethanol are mixed and stirred to obtain solution A; N, N-dimethylformamide, dimethyl sulfoxide and polyvinyl pyrrolidone are mixed and stirred to obtain solution B; solution A and solution B are mixed and stirred to obtain spinning solution; the spinning solution is subjected to electrostatic spinning or solution air spinning to obtain a precursor film, and the precursor film is subjected to air annealing to obtain a flexible continuous nano-glass fiber cloth.
[0011] Preferably, the annealing temperature is 650°C-850°C.
[0012] Preferably, during the electrospinning process, a disordered nonwoven structure is obtained by a flat collector, and an oriented distributed structure is obtained by a rotating drum.
[0013] Preferably, in step 5, a solvent is also added to the impregnation liquid.
[0014] Preferably, the prepolymer is one or a combination of polyacrylate, epoxy resin, and polyurethane.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a lithium battery composite diaphragm with high heat resistance and high breakdown field strength. The diaphragm comprises a flexible continuous glass fiber skeleton and a light irradiation cross-linked and cured polymer. The flexible continuous glass fiber skeleton is embedded in a three-dimensional cross-linked organic polymer coating layer, which is a "flexible continuous glass fiber skeleton" + "three-dimensional cross-linked organic functional layer coating". The composite diaphragm has the following advantages. First, the flexible continuous glass fiber skeleton is a flexible material. Since the flexible continuous glass fiber skeleton is embedded in the light-irradiated cross-linked curing polymer, the two have good bonding, making the diaphragm itself integrated, and the entire diaphragm continuous glass fiber skeleton has the characteristics of high modulus and high porosity; second, the three-dimensional cross-linked organic polymer coating is a photocuring material. Both the flexible continuous glass fiber skeleton and the three-dimensional cross-linked organic polymer coating have high heat resistance, which increases the heat resistance temperature of the composite diaphragm to nearly 350°C; third, the three-dimensional cross-linked organic polymer coating has good electrical insulation properties, giving the composite diaphragm a very high breakdown field strength (>140kV / mm), which is significantly improved compared to commercial polyolefin diaphragms (~50kV / mm); fourth, the three-dimensional cross-linked organic polymer coating has the characteristics of electrochemical stability, adjustable pores, good adhesion to the electrode, and rapid curing at room temperature, so that the composite diaphragm has good electrochemical properties and excellent preparation convenience. The diaphragm prepared by the present invention can meet the requirements of high structural stability, high safety, high reliability, and excellent mechanical properties of lithium batteries, has good electrochemical properties, and has a simple preparation process. It has high application value in scenarios such as large-scale energy storage and electric vehicles.
[0016] The present invention also discloses a method for preparing a high-heat-resistant and high-breakdown field strength lithium battery composite diaphragm, the preparation method comprising the following steps: (1) selecting a flexible continuous nano-glass fiber cloth or a flexible alkali-free ultrafine glass fiber cloth as a flexible continuous glass fiber skeleton; (2) preparing a high-temperature and high-voltage resistant polymer prepolymer impregnation liquid that can be cross-linked and cured by light irradiation; (3) using the flexible continuous nano-glass fiber cloth in step (1) as the diaphragm skeleton, fully impregnating it with the impregnation liquid in step (2), and then irradiating and curing it into a film to obtain a high-temperature and high-voltage resistant lithium battery composite diaphragm. In the light curing process of this method, the small molecules in the prepolymer can react with the hydroxyl groups on the surface of the flexible continuous glass fiber skeleton in situ, so that the binding force between the two is strong, and the diaphragm finally prepared can avoid the problems of inorganic coating shedding and powder falling. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope photo of a typical composite diaphragm; Figure 2 Comparison of heat resistance between typical composite diaphragms and commercial polyolefin diaphragms. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0019] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0020] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0021] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0022] The invention discloses a lithium battery composite diaphragm with high heat resistance and high breakdown field strength, which is composed of a flexible continuous glass fiber skeleton and a three-dimensional cross-linked organic polymer coating layer.
[0023] Preferably, the flexible continuous glass fiber skeleton is composed of one or both of flexible continuous nano-glass fiber cloth and flexible alkali-free ultra-fine glass fiber cloth.
[0024] Among them, the flexible continuous nano glass fiber cloth is based on the spinning solution, and is obtained by annealing after electrostatic spinning or solution gas spinning to form a film. Flexible alkali-free ultrafine glass fiber cloth, referred to as alkali-free glass fiber cloth, is a flexible material made of alkali-free glass fiber yarn through a special process. The alkali metal oxide content of alkali-free glass fiber is extremely low, and the chemical composition is mainly aluminum borosilicate. The flexible alkali-free ultrafine glass fiber cloth of the present invention can be prepared in the laboratory or directly purchased.
[0025] Preferably, the diameter of the flexible continuous nanoglass fiber cloth is 100-400nm, the thickness is 5-50 microns, and the structure is an oriented distribution structure or a disordered non-woven structure. The smaller the diameter of the flexible continuous nanoglass fiber cloth, the better the macro flexibility, the higher the tensile strength and modulus, and the more conducive to the adjustment of the membrane porosity, but the greater the difficulty of preparation. The fiber preparation process involved in the present invention can batch prepare fibers of about 100-400nm, and can ensure flexibility.
[0026] Preferably, the flexible alkali-free ultrafine glass fiber cloth has a diameter of 0.1-8 microns, a thickness of 5-50 microns, and a positive interlaced structure.
[0027] The thickness of the above-mentioned flexible continuous nano-glass fiber cloth and flexible alkali-free ultra-fine glass fiber cloth is 5-50 microns. The thinner the diaphragm, the worse the tensile strength. The thicker the diaphragm, the greater the surface density. Too thick is not conducive to the energy density of the battery. Therefore, setting the thickness to 5-50 microns can basically ensure that the thickness and surface density of the diaphragm meet the basic requirements of battery diaphragms.
[0028] Preferably, the three-dimensional cross-linked organic polymer coating layer is composed of a photoirradiation cross-linked and cured polymer.
[0029] The present invention also discloses a method for preparing a high temperature and high voltage resistant lithium battery composite diaphragm, comprising the following steps: Step 1, preparing a flexible continuous nano-glass fiber cloth as a flexible continuous glass fiber skeleton, or directly laminating a flexible alkali-free ultra-fine glass fiber cloth as a flexible continuous glass fiber skeleton; Step 2, mixing the light irradiation cross-linking and curing polymer raw materials uniformly to obtain an impregnation solution, wherein the light irradiation cross-linking and curing polymer raw materials include a prepolymer, a photoinitiator and a pore-forming agent; Step 3, laying the flexible continuous nano-glass fiber cloth or the flexible alkali-free ultra-fine glass fiber cloth on the substrate, and applying the impregnation liquid droplets obtained in step 2 on the flexible continuous glass fiber skeleton, and completely soaking the glass fiber skeleton; Step 4, placing it under a high-energy light source for irradiation to solidify it, thereby obtaining a high-temperature and high-voltage resistant lithium battery composite separator.
[0030] In the above process, a flexible continuous glass fiber skeleton is placed on a substrate, and the flexible continuous glass fiber skeleton is completely impregnated and wrapped with an impregnation liquid containing a light-irradiated cross-linked curing polymer as the main raw material. Under light conditions, the light-irradiated cross-linked curing polymer can react in situ to undergo photocuring to form a lithium battery composite diaphragm.
[0031] In some embodiments of the present invention, the flexible continuous nano glass fiber cloth in step 1 is based on the spinning solution, formed into a film by electrospinning or solution gas spinning, and then post-treated by air annealing, and the annealing temperature is 650°C-850°C. During the annealing process, the carrier polymer in the original spinning fiber PVP-polysiloxane is removed, leaving only Si and O inorganic components, and at the same time, the -Si-O-Si-inorganic network is reconstructed during the annealing process to form amorphous SiO2. The annealing temperature and procedure are crucial to the flexibility and amorphous structure of the fiber. Annealing temperatures above 1000°C may cause fiber crystallization, and too low annealing temperatures are not conducive to the removal of the carrier polymer and the reconstruction of the -Si-O inorganic network.
[0032] The annealing process of the present invention is divided into three stages of annealing, the annealing temperature is from low to high, the temperature is slowly heated to a first set temperature (about 200°C) and maintained for a set time, heated from the first set temperature to a second set temperature (about 400°C) and maintained for a set time, and heated from the second set temperature to a third set temperature (about 600°C) and maintained for a set time; wherein the first stage can remove residual unreacted TEOS, the second stage can remove the polymer carrier and fiber refinement (diameter reduction), and the third stage can completely convert the inorganic precursor fiberization into amorphous SiO2 fibers.
[0033] For example, in a specific embodiment, the annealing stage is divided into three stages: 1) heating from 20°C to 180°C, with a heating rate of 1°C / min, and keeping at 180°C for 2 hours; 2) heating from 180°C to 325°C, with a heating rate of 1°C / min, and keeping at 325°C for 2 hours; 3) heating from 325°C to 750°C, with a heating rate of 1°C / min, and keeping at 750°C for 2 hours, and then the heating is terminated. In this process, the purpose of keeping at 180°C is to remove the residual unreacted TEOS, the purpose of keeping at about 325°C is to remove the polymer carrier and achieve fiber thinning (diameter reduction), and the purpose of keeping at about 750°C is to completely convert the inorganic precursor fiber into amorphous SiO2 fiber.
[0034] In a specific embodiment, electrospinning specifically includes the following steps: Step 1.1, preparing spinning solution; Tetraethyl silicate (TEOS), dilute hydrochloric acid (HCl, prepared by adding three drops of concentrated hydrochloric acid to 25 ml of deionized water), and ethanol (EtOH) were mixed and stirred at room temperature for 12 hours to fully hydrolyze TEOS to obtain solution A; a certain amount of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solvents were weighed, and then a certain amount of polyvinyl pyrrolidone (PVP) was added to the above mixed solvent, and the PVP was fully stirred to completely dissolve to obtain solution B; the above solution A was slowly added to solution B, and the spinning solution was fully stirred for 1 hour. The mass fractions of TEOS, PVP, HCl, EtOH, DMF, and DMSO were 13.3%, 9%, 5.3%, 2.9%, 53.5%, and 16%, respectively.
[0035] Step 1.2: Electrospinning to obtain precursor membrane The spinning solution is loaded into a syringe, and spinning is performed through a flat collector or a rotating drum to obtain an electrospinning precursor film. The electrospinning precursor film obtained by electrospinning in the present invention is a sheet-like object formed by meshing and bonding. Different from conventional chopped yarns, the yarns in the precursor film prepared in the present invention are filaments. The fibers in the precursor film prepared in the present invention are continuous fibers, and continuous flexible glass fibers with infinite aspect ratio can be obtained after annealing.
[0036] The disordered nonwoven structure is obtained by the flat plate collector. The disordered nonwoven structure refers to a structure in which the fibers are arranged randomly, chaotically or in a disordered state.
[0037] The electrospinning precursor film obtained by rotating drum spinning is an oriented distribution structure. The oriented distribution structure refers to the specific arrangement direction of the fibers formed during the preparation process. By controlling the electrospinning process parameters and the collection device, nanofibers with different orientation distributions can be obtained. These fibers can present a variety of orientation forms such as random arrangement, parallel arrangement, and cross arrangement. In the specific preparation process, a layer of precursor film is first obtained by rotating the drum, and a layer of precursor film is collected after a set time interval. The precursor film with an orthogonal interlaced structure is obtained by orthogonally stacking according to the set fiber orientation direction.
[0038] Step 1.3, annealing and pyrolyzing the precursor film at a temperature of 650°C-850°C.
[0039] In some embodiments of the present invention, the prepolymer in step 2 is one or a combination of polyacrylate, epoxy resin, and polyurethane.
[0040] In some embodiments of the present invention, the photoinitiator in step 2 is a free radical initiator (such as 369, 819 and TPO), a cationic initiator (such as UV16976 and UV16922), or a macromolecular initiator (such as SR1130 and OmnipolTX), and the ratio of the initiator is 0.1-5wt%.
[0041] In some embodiments of the present invention, a solvent can be added to the impregnating liquid. When the viscosity of the impregnating liquid is high, the solvent is added to adjust the viscosity.
[0042] In some embodiments of the present invention, the mass fraction of the prepolymer in step 2 is 30-80%, the mass fraction of the pore former is 30-80wt%, and the mass fraction of the solvent is 10-50wt%. In the present invention, there is no particular restriction on the types of solvents and pore formers in step 2. However, it should be understood that the pore former, photoinitiator and solvent should all match the prepolymer to ensure that the prepolymer can be smoothly photocured. Since the flexible continuous glass fiber skeleton itself has certain holes, the introduction of the pore former during the photocuring process can further adjust the size and number of holes in the three-dimensional cross-linked organic polymer coating layer on the basis of the holes of the flexible continuous glass fiber skeleton, and the distribution of the pores is more uniform, meeting the set requirements, and the pores formed by the inorganic skeleton are smaller and more uniform.
[0043] In some embodiments of the present invention, the substrate in step 3 is a hard, high-transmittance, high-flatness plate made of quartz glass, organic glass, or a high-transmittance resin plate.
[0044] It should be understood that when the impregnating liquid is dripped onto the flexible continuous glass fiber skeleton, it is necessary to ensure that the impregnating liquid can completely cover and soak the flexible continuous glass fiber skeleton, so that all of the flexible continuous glass fiber skeleton is in the impregnating liquid.
[0045] Preferably, the high energy light source in step 4 is a high pressure mercury lamp, an LED ultraviolet light source, or a xenon flash lamp.
[0046] The following is further described in conjunction with specific embodiments.
[0047] Example 1 Preparation of flexible continuous nano-glass fiber cloth: 7.24g tetraethyl silicate, 2.9g dilute hydrochloric acid (prepared by adding three drops of concentrated hydrochloric acid to 25ml deionized water), and 1.55g ethanol were mixed and stirred at room temperature for 12h to fully hydrolyze TEOS to obtain TEOS solution; 29.18g DMF and 8.75g DMSO were mixed, and 4.9g PVP was added to the mixture, and the PVP was fully dissolved by stirring to obtain a polymer template solution. The TEOS solution was slowly added to the polymer template solution and stirred for 1h to obtain the spinning solution required for electrospinning. The spinning solution was loaded into a 20ml syringe for electrospinning. The spinning conditions were: voltage 15kv, distance between the flat collector and the needle was 20cm, solution feed rate 1ml / h, temperature 25±3℃, humidity 20±5%. According to the electrospinning time, an electrospinning precursor membrane of the required thickness was prepared. The precursor membrane obtained by spinning was placed in a muffle furnace for pyrolysis, and the heating program was as follows: 1) heating from 20°C to 180°C at a heating rate of 1°C / min; 2) keeping warm at 180°C for 2h; 3) heating from 180°C to 325°C at a heating rate of 1°C / min; 4) keeping warm at 325°C for 2h; 5) heating from 325°C to 800°C at a heating rate of 1°C / min; 6) keeping warm at 800°C for 2h; 7) ending the heating and cooling down to room temperature with the furnace to obtain a flexible continuous electrospun nanoglass fiber nonwoven base membrane (EGNF).
[0048] Preparation of composite membrane: Weigh appropriate amounts of 1,4-butanediol diacrylate (BD) and ethylene carbonate (EC, pore-forming agent), mix the two at room temperature in a mass ratio of 4:6, add 0.1wt% of 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl) butanone (photoinitiator 369) to the mixed solution, and place it in a 50°C oil bath for heating and stirring until it is completely dissolved to obtain a photocurable impregnation solution. Take an EGNF base film of about 25μm as the skeleton, lay it flat on a transparent polypropylene film (PP film), drop the above photocurable solution on the EGNF base film to make it completely infiltrated with the base film, and clamp it with two transparent glass plates to keep it flat and uniform in thickness, and then use an LED ultraviolet light curing instrument to irradiate the front and back for 4 minutes to complete the curing. Peel off the cured composite membrane from the PP film to obtain a composite membrane.
[0049] Example 2 Preparation of flexible continuous nano-glass fiber cloth: 7.24g tetraethyl silicate, 2.9g dilute hydrochloric acid (prepared by adding three drops of concentrated hydrochloric acid to 25ml deionized water), and 1.55g ethanol were mixed and stirred at room temperature for 12h to fully hydrolyze TEOS to obtain TEOS solution; 29.18g DMF and 8.75g DMSO were mixed, and 4.9g PVP was added to the mixture, and the PVP was fully dissolved by stirring to obtain a polymer template solution. The TEOS solution was slowly added to the polymer template solution and stirred for 1h to obtain the spinning solution required for electrospinning. The spinning solution was loaded into a 20ml syringe for electrospinning. The spinning conditions were: voltage 20kv, the distance between the rotating drum collector and the needle was 15cm, the solution feed speed was 0.5ml / h, the drum speed was 2000rpm / min, the temperature was 25±3℃, and the humidity was 20±5%. The precursor membrane was collected every 10 minutes during electrospinning, and the precursor membrane with an orthogonal interlaced structure was obtained by orthogonal stacking along the fiber orientation direction, and then placed in a muffle furnace for pyrolysis. The heating procedure was as follows: 1) heating from 20°C to 180°C at a heating rate of 1°C / min; 2) keeping at 180°C for 2 hours; 3) heating from 180°C to 325°C at a heating rate of 1°C / min; 4) keeping at 325°C for 2 hours; 5) heating from 325°C to 750°C at a heating rate of 1°C / min; 6) keeping at 750°C for 2 hours; 7) ending the heating and cooling to room temperature with the furnace to obtain a flexible continuous electrospun nanoglass fiber nonwoven base membrane (EGNF).
[0050] Preparation of composite diaphragm: Weigh appropriate amounts of S-06E epoxy resin, UV16976 photoinitiator and ethyl acetate solvent, mix them in a mass ratio of 96:4:50 for 30 minutes to obtain a photocurable impregnation solution. Take an EGNF base film of about 30 μm as the skeleton, lay it flat on a transparent polypropylene film (PP film), drop the above photocurable solution on the EGNF base film to make it completely infiltrated with the base film, and clamp it with two transparent glass plates to keep it flat and uniform in thickness, and then use a high-pressure mercury lamp to irradiate the front and back for 2 minutes each to complete the curing. Peel off the cured composite diaphragm from the PP film to obtain a composite diaphragm.
[0051] Example 3 Preparation of flexible continuous nano-glass fiber cloth: 14.48g tetraethyl silicate, 5.8g dilute hydrochloric acid (prepared by adding six drops of concentrated hydrochloric acid to 50ml deionized water), and 3.1g ethanol were mixed and stirred at room temperature for 12h to fully hydrolyze TEOS to obtain TEOS solution; 58.36g DMF and 17.5g DMSO were mixed, and 9.8g PVP was added to the mixture, and the PVP was fully dissolved by stirring to obtain a polymer template solution. The TEOS solution was slowly added to the polymer template solution and stirred for 1h to obtain a spinning solution. The spinning solution was loaded into an air-blowing spinning instrument, spun at a rate of 5g / hour, and the time was controlled to prepare precursor films of different thicknesses. The precursor membrane obtained by spinning was placed in a muffle furnace for pyrolysis, and the heating program was as follows: heating from 20°C to 325°C at a heating rate of 5°C / min and keeping warm for 2h; heating from 325°C to 850°C at a heating rate of 5°C / min; 6) keeping warm at 850°C for 1.5h; 7) ending the heating and cooling to room temperature with the furnace to obtain a flexible continuous electrospun nanoglass fiber nonwoven base membrane (EGNF).
[0052] Preparation of composite membrane: polyurethane and anhydrous ethanol solvent were mixed in a mass ratio of 50:50, and magnetically stirred at room temperature in the dark for 10 minutes, then 1wt% trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO) was added, and magnetic stirring was continued at room temperature in the dark for 1 hour to obtain a uniform photocurable impregnation solution. An EGNF base film of about 40μm was selected as the skeleton and laid flat on a surface-treated organic glass plate, and the above-mentioned photocurable solution was impregnated on the base film skeleton, and then cured by irradiation with a high-pressure mercury lamp for 5 minutes and then peeled off to finally obtain a composite membrane.
[0053] Example 4 Weigh appropriate amounts of 1,4-butanediol diacrylate (BD) and ethylene carbonate (EC, pore-forming agent), mix the two at room temperature in a mass ratio of 4:6, add 0.1wt% of 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl) butanone (photoinitiator 369) to the mixed solution, and heat and stir in a 50°C oil bath until completely dissolved to obtain a photocurable impregnation solution. Take the EGNF base film of about 20 μm obtained in Example 1 as a skeleton, lay it on an ultra-fine glass fiber cloth (GF, diameter 3 μm, orthogonal structure) with a thickness of about 25 μm, and then lay the GF-EGNF composite base film formed by the two on a transparent resin plate, drop the aforementioned photocurable solution on the GF-EGNF composite base film to make it completely infiltrated with the base film, and clamp it with another transparent resin plate to keep it flat and uniform in thickness, and then use a UV curing instrument to irradiate the front and back sides for 4 minutes to complete the curing. The cured composite diaphragm is peeled off from the resin plate to obtain the composite diaphragm.
[0054] Figure 1This is a scanning electron microscope photograph of the microscopic morphology of a typical composite membrane obtained in Example 4. It can be seen that the composite membrane is composed of nanofibers and a surface-coated polymer layer, and there is a nanoscale pore structure on the polymer. Figure 2 Table 1 shows the heat resistance comparison between the composite diaphragm and the common commercial polyolefin diaphragm. It can be seen that the polyolefin diaphragm undergoes significant thermal shrinkage at around 150°C and completely melts above 250°C, while the thermal stability temperature of the composite diaphragm can reach above 350°C, and the thermal weight loss above 550°C is only 44%. The remaining 56% of the main component is the inorganic component SiO2. According to the literature, the modulus of this main component (>50GPa) is significantly higher than that of the polyolefin diaphragm (1-2GPa). Table 2 shows that the breakdown field strength of the composite diaphragm is greater than 140kV / mm, which is significantly higher than the common commercial polyolefin diaphragm (~50kV / mm). The results in Table 3 show that compared with the polyolefin diaphragm, the composite diaphragm has equivalent or better electrochemical properties, such as higher ionic conductivity and lower battery cycle attenuation rate.
[0055] Table 1 Comparison of DSC and TGA results of typical composite membranes and commercial polyolefin membranes
[0056] Table 2 Breakdown field strength test data of typical composite diaphragms
[0057] Table 3 Electrochemical properties of typical composite membranes and commercial polyolefin membranes
[0058] *Note: Evaluation based on battery assembly of lithium iron phosphate positive electrode and lithium titanate negative electrode, with excess negative electrode.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium battery composite diaphragm with high heat resistance and high breakdown field strength, characterized in that: The diaphragm comprises a flexible continuous glass fiber skeleton and a three-dimensional cross-linked organic polymer coating layer, wherein the flexible continuous glass fiber skeleton is embedded in the three-dimensional cross-linked organic polymer coating layer; The flexible continuous glass fiber skeleton is one or both of a flexible continuous nano glass fiber cloth and a flexible alkali-free ultrafine glass fiber cloth; The flexible continuous nano glass fiber cloth is amorphous SiO2.
2. A lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 1, characterized in that: The flexible continuous nano-glass fiber cloth is composed of a plurality of fibers, the fiber diameter is 100-400 nm, and the thickness of the flexible continuous nano-glass fiber cloth is 5-50 μm.
3. A lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 2, characterized in that: The flexible continuous nano-glass fiber cloth is an oriented distribution structure or a disordered non-woven structure.
4. A lithium battery composite separator with high heat resistance and high breakdown field strength according to claim 1, characterized in that: The diameter of the fibers in the flexible alkali-free ultrafine glass fiber cloth is 0.1-8 μm, and the thickness of the flexible alkali-free ultrafine glass fiber cloth is 5-50 μm.
5. A method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength as claimed in claim 1, characterized in that: The following steps are involved: Step 1, selecting a flexible continuous nano-glass fiber cloth or a flexible alkali-free ultra-fine glass fiber cloth as a flexible continuous glass fiber skeleton; Step 2, mixing the prepolymer, the photoinitiator and the pore-forming agent to obtain an impregnation solution; Step 3, placing the flexible continuous glass fiber skeleton on the substrate, dripping the impregnation liquid on the flexible continuous glass fiber skeleton, and the flexible continuous glass fiber skeleton is immersed in the impregnation liquid; Step 4, irradiating the impregnating liquid and the flexible continuous glass fiber skeleton with a light source, and after the photovoltaic cross-linked cured polymer in the impregnating liquid is cured, a three-dimensional cross-linked organic polymer coating layer is obtained, in which a flexible continuous glass fiber skeleton is embedded, which is a lithium battery composite diaphragm with high heat resistance and high breakdown field strength.
6. The method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 5, characterized in that: In step 1, the preparation method of the flexible continuous nano-glass fiber cloth is as follows: tetraethyl silicate, dilute hydrochloric acid and ethanol are mixed and stirred to obtain solution A; N, N-dimethylformamide, dimethyl sulfoxide and polyvinyl pyrrolidone are mixed and stirred to obtain solution B; solution A and solution B are mixed and stirred to obtain a spinning solution; The spinning solution is subjected to electrostatic spinning or solution air spinning to obtain a precursor film, and the precursor film is subjected to air annealing to obtain a flexible continuous nano glass fiber cloth.
7. The method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 6, characterized in that: The annealing temperature is 650℃-850℃.
8. The method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 6, characterized in that: During the electrospinning process, a disordered nonwoven structure is obtained through a flat collector, and an oriented distributed structure is obtained through a rotating drum.
9. The method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 5, characterized in that: In step 5, a solvent is further added to the impregnation liquid.
10. The method for preparing a lithium battery composite diaphragm with high heat resistance and high breakdown field strength according to claim 5, characterized in that: The prepolymer is one or a combination of polyacrylate, epoxy resin and polyurethane.
Citation Information
Patent Citations
Separator for electrochemical element and fabrication method for same
CN104272503A
Compound lithium-ion battery diaphragm and preparation method thereof
CN104362278A
High-safety compound lithium battery diaphragm and preparation method thereof
CN107819095A
Organic-inorganic composite lithium ion battery diaphragm and preparation method thereof
CN115693027A